2008
DOI: 10.1007/s10096-008-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial resistance surveillance in China: a report from Mohnarin 2004–2005

Abstract: The aim of this study was to establish a nationwide antimicrobial resistant surveillance network and obtain information on bacterial resistance in China. A total of 4075 clinical bacterial isolates were collected from 17 hospitals in 15 cities throughout China. Antibacterial minimal inhibitory concentrations (MICs) were determined by the standard agar dilution method recommended by Clinical and Laboratory Standards Institute. The results of the MICs revealed the following bacterial resistance characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 13 publications
4
51
1
1
Order By: Relevance
“…Our study revealed high resistance to tetracycline, ampicillin, amoxicillin/clavulanic acid, trimethoprimsulfamethoxazole, gentamicin, and enrofloxacin, and showed a similar pattern found in another study among E. coli isolates from companion animals in China [20]. The resistance rate to fluoroquinolones (60.9%) was similar to that found in previous studies among foodproducing animals and humans in China [21,22], while it was significantly greater than the fluoroquinolone resistance rates (about 10%) in companion animals in the United States and Portugal [23,24]. Increased fluoroquinolone resistance can limit the treatment of E. coli infection in companion animals, and in turn may limit the treatment options in humans, who may contract E. coli infections from their pets.…”
Section: Discussionsupporting
confidence: 89%
“…Our study revealed high resistance to tetracycline, ampicillin, amoxicillin/clavulanic acid, trimethoprimsulfamethoxazole, gentamicin, and enrofloxacin, and showed a similar pattern found in another study among E. coli isolates from companion animals in China [20]. The resistance rate to fluoroquinolones (60.9%) was similar to that found in previous studies among foodproducing animals and humans in China [21,22], while it was significantly greater than the fluoroquinolone resistance rates (about 10%) in companion animals in the United States and Portugal [23,24]. Increased fluoroquinolone resistance can limit the treatment of E. coli infection in companion animals, and in turn may limit the treatment options in humans, who may contract E. coli infections from their pets.…”
Section: Discussionsupporting
confidence: 89%
“…Strains sensitive to antimicrobial drugs are inhibited, resulting in significant proliferation of drug-resistant strains and nosocomial infection. [7] A. baumannii infections accounted for 39.13% of gram-negative bacterial infections, which is similar to the result of sputum culture performed during the same period in our hospital. We believe these infections were nosocomial, possibly the result of poor hand hygiene during day-to-day care and contamination of the three-way tap of the infusion set.…”
Section: Discussionsupporting
confidence: 84%
“…The wide use of aggressive antibiotic treatments in CF disease has resulted in an increased risk of emergent antibiotic resistance, as demonstrated in the pathogens S. aureus and P. aeruginosa [6]. The monitoring of bacterial resistance to antimicrobial agents may therefore provide scientific information that would be useful in developing guidelines for the rational use of antibiotics to prevent drug resistance.…”
Section: Introductionmentioning
confidence: 99%